Fusion SPOT-5 & Radarsat-1 images for mapping major bee plants in Marang district, Malaysia. - Saberioon, M. M.; Mardan, M.; Nordin, L.; Mohd Sood, A.; Gholizaeh, A. (European Journals, Inc., 2009)
Melaleuca Cajuputi and Acacia Auriculiformis trees are major sources of nectar and pollen for A. dorsata and the colonies are a major source of honey to the rural poor honey hunters. Honey is a supplementary income to many of these people (including school children) in the Marang district, Terengganu. Apis dorsata colonies are hunted during the honey season in flowering period between May to October. Increase in the number of honey hunters in Marang area shows the importance of Apis dorsata and its honey for local people. To make any decision for improving honey products from Apis dorsata, vegetation mapping is essential to provide information about trees and flowers which are sources of nectar and pollen for Apis dorsata. In this study, Marang area with 270 square kilometers was chosen as pilot study area in Terengganu state for mapping Melalueca Cajuputi and Acacia auriculiformis as two dominant species in low land secondary forest. To inventory and produce land use map of Melaleuca forest in Marang area, in this study SPOT-5 satellite image in multispectral mode with 10 meter resolution which acquired in 2007 as optical satellite were utilized. Most images from optical satellites had some null data from ground because of clouds and shadow of clouds. To solve this problem, Hue, Saturation and value (HSV) and Principal Component Analysis (PCA) were used as fusion techniques to replace null data with microwave data which taken from Radarsat-1 image in C-band with 25 meter resolution image. Accordingly, fusion techniques which were used in this research show that statistically fusion technique has better result than color related technique for mapping Melaleuca forest.